2015
DOI: 10.1021/ol503689r
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Diastereoselective Oxyarylation of 2-Alkylindoles

Abstract: Diastereoselective oxyarylation of N-protected 2-alkylindoles with commercially available boronic acids and TEMPO as a mild oxidant to give N-protected 2-aryl-2-alkyl-3-(2-chloroacetoxy)indolines is described. Reactions are easy to conduct, and product indolines containing a fully substituted C-center are obtained in good yields with good to excellent selectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 35 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…The mixture was stirred at room temperature for 5 min followed by the addition of CuI (0.0676 g, 0.3 mmol). After being stirred at room temperature for 12 h as monitored by TLC, the resulting suspension was filtered under vacuum, concentrated and purified by column chromatography on silica gel (petroleum ether/ethyl acetate=60/1) to afford 7b as an oil; yield: 5.4148 g (88%). 1 H NMR (400 MHz, CDCl 3 ): δ =7.25 (dd, J 1 =7.6 Hz, J 2 =1.2 Hz, 1 H, ArH), 7.10–7.04 (m, 1 H, ArH), 6.70–6.63 (m, 2 H, ArH), 4.16 (bs, 2 H, NH 2 ), 2.36 (d, J =6.4 Hz, 2 H, CH 2 ), 1.98–1.87 (m, 1 H, CH), 1.05 (d, J =6.8 Hz, 6 H, 2×CH 3 ); 13 C NMR (100 MHz, CDCl 3 ): δ =147.6, 132.0, 128.7, 117.8, 114.1, 109.0, 94.6, 77.8, 28.8, 28.2, 22.0; MS (%): m / z =173 (M + , 49.5), 130 (100); IR (neat): ν =3473, 3377, 3028, 1612, 1572, 1492, 1455, 1426, 1384, 1367, 1343, 1305, 1263, 1245, 1157 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was stirred at room temperature for 5 min followed by the addition of CuI (0.0676 g, 0.3 mmol). After being stirred at room temperature for 12 h as monitored by TLC, the resulting suspension was filtered under vacuum, concentrated and purified by column chromatography on silica gel (petroleum ether/ethyl acetate=60/1) to afford 7b as an oil; yield: 5.4148 g (88%). 1 H NMR (400 MHz, CDCl 3 ): δ =7.25 (dd, J 1 =7.6 Hz, J 2 =1.2 Hz, 1 H, ArH), 7.10–7.04 (m, 1 H, ArH), 6.70–6.63 (m, 2 H, ArH), 4.16 (bs, 2 H, NH 2 ), 2.36 (d, J =6.4 Hz, 2 H, CH 2 ), 1.98–1.87 (m, 1 H, CH), 1.05 (d, J =6.8 Hz, 6 H, 2×CH 3 ); 13 C NMR (100 MHz, CDCl 3 ): δ =147.6, 132.0, 128.7, 117.8, 114.1, 109.0, 94.6, 77.8, 28.8, 28.2, 22.0; MS (%): m / z =173 (M + , 49.5), 130 (100); IR (neat): ν =3473, 3377, 3028, 1612, 1572, 1492, 1455, 1426, 1384, 1367, 1343, 1305, 1263, 1245, 1157 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Of note, this interesting indene transformation was successfully also used in a total synthesis of a resveratrol-based natural product . For C2-substituted indoles or benzofurans, carboxylic acids can be added to trap intermediates of type B . The trapping with an acid can also be realized intramolecularly …”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…Recently, Itami et al reported synthesis of 2‐aryl‐3‐acyloxy‐2,3‐dihydrobenzofurans by treating benzofurans, arylboronic acids and carboxylic acids in the presence of Pd(OAc) 2 and 2,2,6,6‐tetramethylpiperidine oxide (TEMPO) (Scheme ) . In another effort, Studer group have described the Pd(OAc) 2 ‐catalyzed oxyarylation of N ‐protected 2‐alkylindoles by arylboronic acids and chloroacetic acid in the presence of TEMPO as a mild oxidant (Scheme ) . Both Itami and Studer reports include acyloxyarylation of electron‐rich alkenes.…”
Section: Introductionmentioning
confidence: 99%